Identification of a binding pocket of letermovir in the terminase subunit pUL56 of human cytomegalovirus - Lukas M. Kmetsch; Hans Tietze; Elke Bogner (Scientific Reports)
Abstract A key step in replication of human cytomegalovirus (HCMV) is the generation and packaging of unit-length genomes into preformed capsids. The enzymes involved in this process are viral terminases. The HCMV terminase consists of two subunits, the ATPase pUL56 and the nuclease pUL89. A potential third component, pUL51, has been proposed. Letermovir is the first terminase inhibitor available for HCMV prophylaxis to allogenic hematopoietic stem cell recipients. However, mutations in the HCMV terminase subunit pUL56 and, to a lesser extent, in pUL89 or pUL51 lead to resistance. Here we focused on the drug target area in the terminase subunit pUL56. To gain further structural insights into the putative binding site of letermovir, in silico analysis of the structure was performed using Phyre2 and SwissDock. For our analysis, we used three of the most frequent mutations during letermovir treatment, C325F, C325Y and C325W. We demonstrated that all variants have a pronounced cavity reduction, leading to the letermovir binding conformations being “pushed-out” of the binding pocket. This results in a changed distribution of the Gibbs free binding energy. To circumvent the absolute resistance of C325 mutations a further modification of letermovir might solve the problem and leads to optimizing drug targeting capacity.